Baeuveria bassiana (Bals)Vuill and Metarhizium anisioplae (Metsch.) Sorokin in the pupas control of Prodiplosis longifila Gagné on asparagus crop - Cedano, Carolina (2012)
The objective of the present work was to evaluate the effect of the entomopathogen fungi Baeuveria bassiana and Metarhizium anisioplae of the Prodiplosis longifila pupas, in order to reduce the adult population of this insect. The treatments consisted on the application of two different propagel concentrations (mycel and conidia) of each entomopathogen. One of these concentration was 1x106 propagels/ml (obtained from the total amount of conidia collected of 25 kg of rice colonized by the entomopathogen); and the other one, was 1x107 propagels/ml (obtained from the total amount of conidia collected of 40 kg of rice colonized by the entomopathogen). As a check a non application treatment was considered. The applications were trough the irrigation system and started 15 days after the end of harvest and were repeated each five days during a month, coincident with the period of most falls of pupas of the soil. As a result Baeuveria bassiana at 1x107 propagels/ml shown 53.4 % of the total pupas colonized by the entomopathogen, which allows indicating B. bassiana as a promissory biocontrol of this specie.